Access to palliative care in Canada - Johnson, Tracy; Cheng, Clare; Lawand, Christina; Kelly, Maureen (International Journal of Population Data Science, 2018)
Introduction Many Canadians prefer to remain in the community at end-of-life, and to die at home. To do so, early and integrated palliative care (PC) is needed to provide individuals with care and support services across care settings. Measuring access to PC can help to evaluate progress over time. Objectives and Approach This presentation will show findings from our study on whether Canadian decedents had access to PC in the last year of life. Data from physician billings, drug claims, home care, long-term care and acute care were linked to identify decedents and PC service use. These data were also used to examine how PC may affect, or be affected by other interactions with the health system, including inpatient alternate level care days, admissions from long-term care, emergency department visits and stays in intensive care units. Gaps in data availability and quality will also be highlighted. Results About 70% of decedents were identified using administrative health data, although there were variations across jurisdictions due to differences in data availability and quality (9%-81%). For decedents identified across care settings, few received PC in the community in their last year of life, ranging from 4% in long-term care to 12% in home care. More decedents were identified as palliative in acute care (44%) but only one-third received PC in another setting despite multiple interactions with the health system in the last year of life. Those who had integrated, community-based PC were less likely to have a stay in an intensive care unit, and more likely to die in the community. However, few Canadian decedents had access to this type of care. Conclusion/Implications Data linkage identified opportunities for earlier integration of PC and improved care transitions. However, lack of common definitions of PC across sectors and jurisdictions, limitations in data availability and issues in PC coding were identified. Improvements in PC data are required to evaluate progress for the future.